Psychoanalysis and Neuroscience - Mancia, Mauro (Springer Milan : Imprint: Springer, 2006)
The most recent scientific studies have brought a significant contribution to the understanding of basic mental functions such as memory, dreams, identification, repression, which constitute the basis of the psychoanalytical theory. As a matter of fact, numerous neuroscientific observations in recent years have laid the ground for hypotheses on the neurological organization of mental functions that are fundamental to psychoanalytical theory; the discovery of the implicit memory has extended Freud's concept of the unconscious (1915) and highlighted the unrepressed unconscious connected particularly to experiences of the primary relation, stored in the implicit memory. The book focuses on the possibility of interactions between psychoanalysis and neuroscience - i.e., emotions and the right hemisphere, serotonin and depression - and will be a unique tool not only for for professionals and students working in these fields, but also for operators of allied disciplines, such as psychology and psychotherapy.